Ethnography in an emergency room: evaluating patients with alcohol consumption Etnografía en un servicio de urgencias: la valoración de los pacientes con consumo alcohol - Liliana Mondragón; Martha Romero; Guilherme Borges (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE:To present an ethnographic description of the treatment of patients with excessive alcohol consumption in an emergency room, how they are evaluated by doctors, and the various contextual aspects surrounding this condition. MATERIAL AND METHODS: The ethnographic work was carried out over a period of two months, with researchers working 24 hours a day, seven days a week from January 9 to March 15, 2002 in the emergency room (ER) at General Hospital, Mexico City. RESULTS: Patients that had consumed alcohol and were admitted to the ER had to wait longer than others to be treated for their intoxication to wear off and for their sometimes aggressive attitude to become calm. The rejection of the alcoholized patients was expressed through scolding to persuade alcohol-dependent patients or those that abused alcohol to reduce their consumption. CONCLUSION: The theoretical and methodological approach of the ethnographic observation enables reflection on the social and cultural mechanisms related to this health problem. OBJETIVO: Presentar una descripción etnográfica en un servicio de urgencias (su) sobre la atención de los pacientes con consumo excesivo de alcohol, las formas de la valoración de los médicos y los diferentes aspectos contextuales que enmarcan esta condición. MATERIAL Y MÉTODOS: El trabajo etnográfico se realizó durante dos meses, trabajando las 24 horas, los siete días de la semana, del 9 enero al 15 de marzo de 2002, en el servicio de urgencias de un Hospital General de la Ciudad de México. RESULTADOS: Al paciente que había consumido alcohol y que ingresaba al SU se le hacía esperar más, para que se tranquilizara y a su vez disminuyera la intoxicación. A través de regaños se trató de sugerirle al paciente con dependencia o abuso de alcohol que redujera su consumo. CONCLUSIÓN: El abordaje teórico y metodológico de la observación etnográfica permite hacer una reflexión sobre los mecanismos sociales y culturales, enmarcados en las problemáticas de salud.